Structural Dissection of the First Events Following Membrane Binding of the Islet Amyloid Polypeptide - Khemtemourian, Lucie; Fatafta, Hebah; Davion, Benoit; Lecomte, Sophie; Castano, Sabine; Strodel, Birgit (Frontiers in Molecular Biosciences, 2022)
The islet amyloid polypeptide (IAPP) is the main constituent of the amyloid fibrils found in the pancreas of type 2 diabetes patients. The aggregation of IAPP is known to cause cell death, where the cell membrane plays a dual role: being a catalyst of IAPP aggregation and being the target of IAPP toxicity. Using ATR-FTIR spectroscopy, transmission electron microscopy, and molecular dynamics simulations we investigate the very first molecular steps following IAPP binding to a lipid membrane. In particular, we assess the combined effects of the charge state of amino-acid residue 18 and the IAPP-membrane interactions on the structures of monomeric and aggregated IAPP. Distinct IAPP-membrane interaction modes for the various IAPP variants are revealed. Membrane binding causes IAPP to fold into an amphipathic α-helix, which in the case of H18K-, and H18R-IAPP readily moves beyond the headgroup region. For all IAPP variants but H18E-IAPP, the membrane-bound helix is an intermediate on the way to amyloid aggregation, while H18E-IAPP remains in a stable helical conformation. The fibrillar aggregates of wild-type IAPP and H18K-IAPP are dominated by an antiparallel β-sheet conformation, while H18R- and H18A-IAPP exhibit both antiparallel and parallel β-sheets as well as amorphous aggregates. Our results emphasize the decisive role of residue 18 for the structure and membrane interaction of IAPP. This residue is thus a good therapeutic target for destabilizing membrane-bound IAPP fibrils to inhibit their toxic actions.